Pengaruh Model Two Stay Two Stray Berbantuan Canva terhadap Kemampuan Berpikir Kritis Siswa SMPN 1 Sibulue - Riska; Awaluddin, A. Fajar; Wahyuni, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of the Two Stay Two Stray learning model assisted by Canva media on students' critical thinking skills in the subject of Islamic Religious Education for class VII of SMPN 1 Sibulue. This study uses a quantitative approach with a Quasi Experimental Design in the form of a Pre-Test Post-Test Control Group Design. The subjects of this study were all students of class VII of SMPN 1 Sibulue with a population of 68 students. The sampling technique used a purposive sampling technique, class VII A with 22 students as the control class and class VII B with 22 students as the experimental class. The research instrument used was an essay test question to measure students' critical thinking skills. Data analysis includes descriptive statistics and inferential statistics. The results of the study showed a significant difference in the application of the Two Stay Two Stray model assisted by Canva media on students' critical thinking skills in the experimental class. This is proven by the results of the Independent Samples T-Test which shows that there is a significant difference in the average value of students' critical thinking skills between the experimental group and the control group with a calculated t value > t table (4.929 > 2.028) and a significance test of α = 0.05 shows a p value < α (0.001 < 0.05).